Conditional and joint credit risk - André Lucas; Bernd Schwaab; Xin Zhang (European Central Bank (ECB), 2013)
We propose an empirical framework to assess joint and conditional probabilities of credit events from CDS prices observed in the market. Our model is based on a dynamic skewed-t distribution that captures many salient features of CDS data, including skewed and heavy-tailed changes in the price of CDS protection, as well as dynamic volatilities and correlations that ensure that uncertainty and risk dependence can increase in times of stress. We apply the framework to euro area sovereign CDS spreads during the euro area debt crisis. Our results reveal significant time-variation in distress dependence and spill-over effects. We investigate in particular market perceptions of joint and conditional risks around announcements of Eurosystem non-standard monetary policy measures, and document strong reductions in joint risk.
Keywords: C32; G32; 330; financial stability; higher order moments; sovereign credit risk; time-varying parameters